AMELIORATION POTATO PLANT PERFORMANCE UNDER DROUGHT CONDITIONS IN IRAQ BY USING TITANIUM DIOXIDE, AND BIODEGRADING, BIODEGRADABLE TREATMENTS - Aseel M.H. H. Al-Khafaji; Kadhim D. H. Al-jubouri; F. Y. Baktash (Iraqi journal of agricultural science, 2024)
This study was aimed to mitigate the issue of drought in potato production and quality using number of sustainable strategies. The experiment carried out at vegetable field of the College of Agricultural Engineering Sciences - University of Baghdad during spring season 2023. The experiment was conducted using split arrangement within Randomized Complete Block Design with two factors and three replicates (2X6X3). Applying TiO2-NPs represented the first factor (main plot) (10 mg.L-1), which symbolized (T0, T1). six treatments were included to represent subplots (regular irrigation interval (I) prolonged irrigation interval (D), fungal biofertilizers (DB), fungal biofertilizers + mannitol (DBM), fungal biofertilizers +xanthan (DBZ), fungal biofertilizers + mannitol+ xanthan (DBMZ). Results showed the superiority of spraying TiO2-NPs in all yield traits. Also the results revealed interaction treatment T1DBMX in producing significant results the entire vegetative growth traits and stress related enzymes concentrations in compare to control treatment T0D.